2017
DOI: 10.18393/ejss.306698
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of nitrogen and zinc to bio-fortify zinc in wheat grains

Abstract: Article Info Received : 24.01.2017 Accepted : 07.04.2017 Our daily diet is largely contributed by cereals, which have low genetic abilities to amass higher concentrations of micronutrients in their grains. Hence, wide spread deficiencies iron, zinc and other essential nutrients have prevailed. Present study focuses the biofortification of Zn in wheat grains, taking advantage of nutrient-nutrient synergy between Zn and N. Three wheat genotypes (NIA-Amber, BWQ-4 and SD-998) were tested in a field experiment fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
4
10
0
Order By: Relevance
“…Cakmak et al (2010) explained role of improved protein synthesis and activity due to better enzymatic functions in plants, in increasing Zn concentration in vegetative parts and Zn translocation into grains. Kutman et al (2012), Barunawati et al (2013), Sperotto et al (2013) and Akram et al (2017) also found similar results when Zn was applied to different crops. Phytic acid is indigestible in human yet, its concentration is important for grain vigor and plant functions.…”
Section: Discussionsupporting
confidence: 54%
“…Cakmak et al (2010) explained role of improved protein synthesis and activity due to better enzymatic functions in plants, in increasing Zn concentration in vegetative parts and Zn translocation into grains. Kutman et al (2012), Barunawati et al (2013), Sperotto et al (2013) and Akram et al (2017) also found similar results when Zn was applied to different crops. Phytic acid is indigestible in human yet, its concentration is important for grain vigor and plant functions.…”
Section: Discussionsupporting
confidence: 54%
“…However, several researches showed that the lower rate of Zn was more favorable than higher rate in terms of grain yield. Plant height, straw yield, grain yield was improved with increasing rates of N (120 or 150 kg/ha) combined with different levels of Zn (0, 5, 10 kg/ha) than the individual application (Ahmadi et al, 2016;Akram et al, 2017). Maximum emergence, number of tillers, plant height and number of spikes were recorded in plots which were sprayed with 0.5% N, 0.5% K and 0.5% Zn solutions while minimum were recorded in control plots (Gulet al, 2011).There were significant effects of N application on the spike number, the grain number per spike and grain yield as well as Zn application showed significant effect on the spike number, thousand kernel weight and grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Crop residues can have a large effect on soil microbial biomass and activity, which, in turn, affect the ability of soil to supply nutrients to plants through soil organic matter turnover. Microbial biomass carbon has positively correlated with organic carbon content in soil [28,[61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…Dehydrogenase activity, APA-Alkaline phosphatase activity, MBC-Microbial biomass carbonin receiving maximum values of plant growth parameter, yield attributing characteristics, grain yield, soil microbial biomass carbon and dehydrogenase activities at all the growth stages of wheat crop[28,30,[60][61][62][63].Similarly, alkaline phosphatase activity it varied from 148 44. 185.97, 152.27-186.73 and 152.05-186.35 µg para nitrophenol g ) consisting of 100% nitrogen alone, i.e.…”
mentioning
confidence: 99%